2015
DOI: 10.1021/acs.est.5b01967
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sediment Gas Voids and Ebullition on Benthic Solute Exchange

Abstract: The presence of free gas in sediments and ebullition events can enhance the pore water transport and solute exchange across the sediment-water interface. However, we experimentally and theoretically document that the presence of free gas in sediments can counteract this enhancement effect. The apparent diffusivities (Da) of Rhodamine WT and bromide in sediments containing 8-18% gas (Da,YE) were suppressed by 7-39% compared to the control (no gas) sediments (Da,C). The measured ratios of Da,YE:Da,C were well wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 37 publications
(96 reference statements)
0
26
0
Order By: Relevance
“…A large number of porewater profile measurements at different depths and seasons are thus required to reliably quantify average diffusive CH 4 fluxes. This might be facilitated by novel measurement techniques such as porewater sampling by capillary electrophoresis (Torres et al ), but especially in bubbling sediments, the determination of diffusive fluxes remains a difficult task (Flury et al ; Tyroller et al ).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of porewater profile measurements at different depths and seasons are thus required to reliably quantify average diffusive CH 4 fluxes. This might be facilitated by novel measurement techniques such as porewater sampling by capillary electrophoresis (Torres et al ), but especially in bubbling sediments, the determination of diffusive fluxes remains a difficult task (Flury et al ; Tyroller et al ).…”
Section: Discussionmentioning
confidence: 99%
“…While bubbles in cohesive sediment due to methane actually inhibit diffusion of other solutes to the water32, it is suggested that Chaoborus spp. can, through bioturbation, significantly enhance solute flux from sediment to the water column and subsequently increase lake internal loading3.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ebullition could also partially explain the stochastic nature of the water column CH 4 concentrations observed in the archipelago in this study. Not only does ebullition commonly display high spatiotemporal variability (e.g., Scandella et al 2016), it also has been shown to enhance diffusive sedimentary fluxes by making the sediment more porous (Flury et al 2015).…”
Section: Potential Role Of Ebullitionmentioning
confidence: 99%